2005
DOI: 10.1007/s00296-005-0590-1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial functions in Behçet’s disease

Abstract: Behçet's disease (BD) is a systemic vasculitis, capable of involving all types of vessels. Endothelial dysfunction (ED) has been previously documented in BD. The aim of the study was to see whether ED was more prominent in Behçet's patients with vascular involvement (VI) than in those without. The study population consisted of 65 patients with BD, 27 of whom had VI, and 30 healthy controls. High-resolution ultrasound was used to measure endothelium-dependent vasodilatation (EDVD) of brachial artery. Overall, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 16 publications
0
37
0
1
Order By: Relevance
“…Exclusion criteria were reported in 13 studies, 4 of them specified that patients taking drugs interfering with hcy levels were excluded. Thus, 4 studies were considered of high quality, 4,24,25,28 whereas the other 12 were considered of low quality. 8,12,26,27,29 -36 Hyperhomocysteinemia Eight studies, 4,12,26,27,30,32,35,36 for a total of 166 patients with thrombosis and 318 patients without thrombosis, were included in the metaanalysis.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were reported in 13 studies, 4 of them specified that patients taking drugs interfering with hcy levels were excluded. Thus, 4 studies were considered of high quality, 4,24,25,28 whereas the other 12 were considered of low quality. 8,12,26,27,29 -36 Hyperhomocysteinemia Eight studies, 4,12,26,27,30,32,35,36 for a total of 166 patients with thrombosis and 318 patients without thrombosis, were included in the metaanalysis.…”
Section: Study Qualitymentioning
confidence: 99%
“…Eleven studies, 4,8,12,24,25,[27][28][29][30]32,36 for a total of 236 patients with thrombosis and 518 patients without thrombosis, were included in the metaanalysis. In these patients, mean levels of hcy were significantly higher in patients with thrombosis compared with patients without thrombosis (mean difference 3.30 mol/L; 95% CI 2.09 to 4.51; Figure 3), again suggesting an association between the high levels of hcy and the development of thrombosis.…”
Section: Mean Levels Of Homocysteinementioning
confidence: 99%
“…Inflammation materials such as polymorphonuclear leukocytes (PMNs) are activated in RAS,68, 69, 70, 71 and PMNs exhibit increased motility and enhanced adhesion to endothelial cells in vitro 72, 73. Endothelial dysfunction is typical in patients with RAS and BD 74, 75, 76, 77. In such patients, endothelium‐dependent flow‐mediated dilation is reduced and endothelial activation in affected blood vessels mediates vascular inflammation and thrombosis 75, 76.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main findings of the present study is that short-term treatment with nebivolol improves impaired endothelial vasodilator function. Several case-control studies have observed an association between vascular involvement and decreased brachial FMD and increased arterial stiffness in patients with BD (10,(32)(33)(34). Reduced NO production is the one of the possible mechanisms for endothelial dysfunction in BD (11), and the decreased NO production may play a critical role in the impairment of FMD.…”
Section: Discussionmentioning
confidence: 99%